2022
DOI: 10.5114/ada.2021.108429
|View full text |Cite
|
Sign up to set email alerts
|

The role of CYP19A1 and ESR2 gene polymorphisms in female androgenetic alopecia in the Polish population

Abstract: Introduction: Androgenetic alopecia is the most common type of non-cicatricial alopecia both in male and female patients. The mechanism that leads to hair loss is similar in both sexes, but the underlying cause, and especially the role of genes and sex hormones in the pathogenesis of the disease in women has not fully been explained as of yet. So far, a few attempts have been made to assess selected SNPs for CYP19A1 and ESR2 genes, but their results are not unequivocal and fully reproducible. Aim: To investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…In 2021, a study in a Polish population analyzed the association between 13 CYP19A1 and 11 ESR2 gene SNPs and FPHL. The study included 117 FPHL patients and 128 healthy controls, but no significant differences were observed [33]. To sum up, previous studies have shown an association between FPHL and CYP19A1 and ESR2.…”
Section: Sex Steroid Hormones Gene Polymorphismmentioning
confidence: 93%
See 1 more Smart Citation
“…In 2021, a study in a Polish population analyzed the association between 13 CYP19A1 and 11 ESR2 gene SNPs and FPHL. The study included 117 FPHL patients and 128 healthy controls, but no significant differences were observed [33]. To sum up, previous studies have shown an association between FPHL and CYP19A1 and ESR2.…”
Section: Sex Steroid Hormones Gene Polymorphismmentioning
confidence: 93%
“…In the genetic research of FPHL, some studies evaluated specific SNPs of CYP19A1 and ESR2 genes, both of which are related to the transformation of sex hormones [33]. Previous genetic studies have identified associations between FPHL and the ESR2 and CYP19A1 genes.…”
Section: Sex Steroid Hormones Gene Polymorphismmentioning
confidence: 99%